TASAMUH BEHAVIOR IN PERSPECTIVE OF MULTICULTURAL ISLAMIC EDUCATION - Romadlon Chotib; Maskuri Maskuri (Universitas Islam Malang, 2021)
Tasamuh is part of a commendable attitude in association, mutual respect and tolerance between one another starting from opinions, views, beliefs, and habits, with tasamuh being able to respect the differences in society or the nation better especially in countries that have a complex culture such as Indonesia. Tasamuh is an attitude that is highly emphasized in Islam. If this tasamuh of multicultural Islamic education in bahtsul masail, it can become a conference scientific treasure. In this study, the researcher intends to describe, analyze, provide interpretations about; tasamuh of multicultural Islamic education attitudes in bahtsul masail, tasamuh of multicultural Islamic education in bahtsul masail, and multicultural Islamic education values can reinforce the tasamuh bahtsul masail attitude at the Bahtsul Masail Nahdlatul Ulama Institute in East Java. The method that used in this research is qualitative ethnographic type, data collection techniques with participant observation, in-depth interviews, and documentation. The analysis by Miles and Huberman what is called data reduction. After the data was obtained, it was analyzed using descriptive-qualitative method. Next, the conclusions are formulated using deductive methods. To checking the validity of the data used triangulation techniques, member checks, and discussions with colleagues. The result of research in the field show that the values of tasamuh in bahtsul masail can be proven in the form of: tolerance, ta’awwun (help each other), patient and forgiving, friendly (friendly and gentle), easy to accept and respect others, and keep hanging out in a good way even if it’s different. The form of tasamuh behavior that the researchers found in the bahtsul masail were; be generous in all differences, foster a sense of compassion for others, avoid acts of violence and chaos, increase human dignity, maintain social norms and customs, and foster an attitude of responsibility. Multicultural Islamic education values that found in affirming the tasamuh bahtsul masail behavior are in the form of; habituation with al-hiwar (debate dialogue) al-amtsal (parables and images), al-ta’awwud (self-habituation), al-uswah (exemplary), al-ibrah wal-mau’idhah (likeness and reasoning), al-targhib wat-tarhib (pleasing and frightening), as well as with solawat and dhikr.